A novel clutch coupled drive design for rectification of odometry error: a comparative experimental study. (18th May 2021) - Abbas, Ammar Nathad; Samad, Abdul; Ahmed, Shumaila; Siddiqui, Umer Abdullah
Traversing alignment including straight path motion has been one of the major issues in wheeled mobile robots (WMR). Numerous electronic solutions devised to address the precision issues in locomotion lack to account for the mechanical inadequacy from where the error arises. The issue remains when the WMR is made to follow a route over a longer range as the time accumulated deduced (dead) reckoning error produces enough effect in the action that deviates the WMR from the intended route. The WMR thus suffers from systematic odometry problem and fails to actuate through required trajectory in absence of feedback. Fabrication and controlling of a stupendous design for attaining mechanically synchronised drive and to contribute a cost and energy efficient mechanical structure, independent of complicated sensory feedback and algorithm-based control systems is the superior goal of this research. This publication covers a comparative experimental analysis of conventional proportional integral derivative (PID) controller, an in-practice algorithmic solution, with the suggested design.